1996
DOI: 10.1108/eb060667
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Audit Fees: Australian Perspective

Abstract: In line with the guidelines suggested by the Australian Society of Certified Practising Accountants, a sample of 243 Australian listed companies was used in this study to investigate if the factors of auditee size, audit complexity, audit time, audit quality and audit risk could explain the variation of auditor fees. The model achieved a relatively high level of goodness-of-fit (adjusted R equals to 0.7631) and overall significance at p < 0.001 (F-ratio). Like most prior studies, auditee size appeared to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
2
7
2
Order By: Relevance
“…The findings were therefore consistent with the results of studies conducted by Brinn et al (1992) in the UK, Hay et al (2006) in New Zealand, Naser and Nuseibeh (2008) in Jordon, and Thinggaard and Kiertzner (2008) in Denmark, who found that auditee complexity has a significant impact on determining audit fees. However, these results were inconsistent with the findings of Zhang and Myrteza (1996), and Ahmed and Goyal (2005), who found a negative correlation between auditee complexity and audit fees. Auditor size in this study was assumed to be one of the factors that has a positive impact on the variation of audit fees in the AIM machinery equipment companies.…”
Section: Discussion Of the Study's Resultscontrasting
confidence: 93%
See 4 more Smart Citations
“…The findings were therefore consistent with the results of studies conducted by Brinn et al (1992) in the UK, Hay et al (2006) in New Zealand, Naser and Nuseibeh (2008) in Jordon, and Thinggaard and Kiertzner (2008) in Denmark, who found that auditee complexity has a significant impact on determining audit fees. However, these results were inconsistent with the findings of Zhang and Myrteza (1996), and Ahmed and Goyal (2005), who found a negative correlation between auditee complexity and audit fees. Auditor size in this study was assumed to be one of the factors that has a positive impact on the variation of audit fees in the AIM machinery equipment companies.…”
Section: Discussion Of the Study's Resultscontrasting
confidence: 93%
“…The study's finding is consistent with the results of prior researchers who conducted research in different markets, such as Simunic (1980) in the US, Chan et al (1993) in the UK, and Xu (2011) in China. Meanwhile, this result is not in line with studies from Australia by Zhang and Myrteza (1996), in Jordan by Joshi and Al-Bastaki (2000), the US by Francis (1984), and Kuwait by Al-Harshani (2008), who all found a significant positive correlation between auditee risk and audit fees, and addressed auditee risk as an important factor that effects the determination of audit fees. Auditee complexity is about the extent of the audit task.…”
Section: Discussion Of the Study's Resultscontrasting
confidence: 66%
See 3 more Smart Citations